Patient-Reported Barriers to High-Quality, End-of-Life Care: A Multiethnic, Multilingual, Mixed-Methods Study - Periyakoil, Vyjeyanthi S; Neri, Eric; Kraemer, Helena (Journal of palliative medicine, 2016)
The study objective was to empirically identify barriers reported by multiethnic patients and families in receiving high-quality end-of-life care (EOLC). This cross-sectional, mixed-methods study in Burmese, English, Hindi, Mandarin, Tagalog, Spanish, and Vietnamese was held in multiethnic community centers in five California cities. Data were collected in 2013-2014. A snowball sampling technique was used to accrue 387 participants-261 women, 126 men, 133 Caucasian, 204 Asian Americans, 44 African Americans, and 6 Hispanic Americans. Measured were multiethnic patient-reported barriers to high-quality EOLC. A development cohort (72 participants) of responses was analyzed qualitatively using grounded theory to identify the six key barriers to high-quality EOLC. A new validation cohort (315 participants) of responses was transcribed, translated, and back-translated for verification. The codes were validated by analyses of responses from 50 randomly drawn subjects from the validation cohort. All the 315 validation cohort transcripts were coded for presence or absence of the six barriers. In the validation cohort, 60.6% reported barriers to receiving high-quality EOLC for persons in their culture/ethnicity. Primary patient-reported barriers were (1) finance/health insurance barriers, (2) doctor behaviors, (3) communication chasm between doctors and patients, (4) family beliefs/behaviors, (5) health system barriers, and (6) cultural/religious barriers. Age (χ(2) = 9.15, DF = 1, p = 0.003); gender (χ(2) = 6.605, DF = 1, p = 0.01); and marital status (χ(2) = 16.11 DF = 3, p = 0.001) were associated with reporting barriers; and women <80 years were most likely to report barriers to receiving high-quality EOLC. Individual responses of reported barriers were analyzed and only the participant's level of education (Friedman statistic = 2.16, DF = 10, p = 0.02) significantly influenced choices. Multiethnic patients report that high-quality EOLC is important to them; but unfortunately, a majority state that they have encountered barriers to receiving such care. Efforts must be made to rapidly improve access to culturally competent EOLC for diverse populations.